Evaluation of air vents and ramp angles on the performance of orifice spillway aerators - Sarwar, M.K.; Chaudary, Z.A.; Bhatti, Muhammad Tousif; Khan, D. (2016)
The performance of steep slope ( > 30o) orifice spillway aerators by varying air vent size and ramp angles were experimentally studied. Three air vents of different sizes and five ramps with different angles were tested on a physical model of Bunji dam spillway, which was constructed at Irrigation Research Station Nandipur, Gujranwala. In each case, the cavity length, cavity pressure, flow velocity and water depth at the aerator were measured by changing operating conditions. Non-dimensional jet length ( ), air entrainment co-efficient (ß) and non-dimensional cavity pressure (Pn) were computed to evaluate the performance of the aerator against ramp angle and air vent size. Results noted an improvement in the performance of aerator with the increase of air vent size. However, the ramp initially improved the performance of the aerator but at higher reservoir level with large gate opening, no significant improvement in the performance of the aerator was noted, rather negative impact was observed due to reduction in cavity pressure.